2015
DOI: 10.1186/s13069-015-0032-y
|View full text |Cite
|
Sign up to set email alerts
|

Cytoglobin expression in the hepatic stellate cell line HSC-T6 is regulated by extracellular matrix proteins dependent on FAK-signalling

Abstract: BackgroundFibrosis is a physiological response to cellular injury in the liver and is mediated by the activation of hepatic stellate cells resulting in the replacement of hepatocytes with extracellular matrix comprised principally of collagen 1 to form a hepatic scar. Although the novel hexaco-ordinated globin cytoglobin was identified in activated hepatic stellate cells more than 10 years ago, its role in stellate cell biology and liver fibrosis remains enigmatic.ResultsIn the current study, we investigated t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 65 publications
0
10
0
Order By: Relevance
“…Co-staining of Thy-1 and CD248 was detected in isolated human hepatic stellate cells [87]. It has been reported that cytoglobin expression is correlated with a more quiescent phenotype of HSCs and is regulated by extracellular matrix proteins dependent on FAK signaling in rat HSC-T6 cell line [88].…”
Section: Cygb/stap (Cytoglobin/stellate Cell Activation-associated Prmentioning
confidence: 93%
“…Co-staining of Thy-1 and CD248 was detected in isolated human hepatic stellate cells [87]. It has been reported that cytoglobin expression is correlated with a more quiescent phenotype of HSCs and is regulated by extracellular matrix proteins dependent on FAK signaling in rat HSC-T6 cell line [88].…”
Section: Cygb/stap (Cytoglobin/stellate Cell Activation-associated Prmentioning
confidence: 93%
“…In contrast, the iPSc-derived HSCs incubated without EVs or with MM plasma-derived EVs exhibited a more rounded morphology suggestive of a more quiescent state ( Figure 4B). The activation status of HSCs was determined by quantifying α-SMA and Col1A1 mRNA expression, markers of stellate cell activation (27). They were found to be signi cantly increased by incubation with ZZ plasma-derived EVs after 24 hours compared to control and MM plasma-derived EV treatment ( Figure 4C).…”
Section: Comparison Of Ev-associated and Plasma Cytokines And Chemokimentioning
confidence: 99%
“…In Xu et al [ 103 ], overexpression of Cygb protected primary rat HSCs against oxidative stress, as assessed by reduced production of malondialdehyde and 4-hydroxynonenal, biomarkers of lipid peroxidation. In Stone et al [ 154 ], Cygb expression was correlated with a more quiescent phenotype of stellate cells in culture and Cygb was regulated by the extracellular matrix through integrin signaling in a manner dependent on activation of focal adhesion kinase. Consistently, in human liver tissues damaged by HCV infection at various fibrosis stages, the number of Cygb-positive cells decreases with fibrosis progression [ 37 ].…”
Section: Cygb Suppresses Hsc Activation and Fibrosis Developmentmentioning
confidence: 99%